Are we ready for mobile payment? / Seuk Wai Phoong … [et al.] - Wai Phoong, Seuk; Yen Phoong, Seuk; Moghavvemi, Sedigheh; Chung Yeong, Wai (Universiti Teknologi MARA, Shah Alam, 2019)
This study aims to identify the factors influencing the readiness and acceptance of mobile payment applications. The study is performed using the survey method. Quantitative data analysis are used to measure the relationship between the perceived usefulness, perceived ease of use, and perceived security on the readiness of Malaysian in using mobile payment applications. The results shown that perceived usefulness, perceived ease of use, and perceived security have a positive and significance relationship with the usage of mobile payment applications. Moreover, perceived ease of use is reported as the strongest factor towards usage of mobile payment applications, following by perceived security and perceived usefulness. This study is able to provide information on the current stage of use on mobile payment in Malaysia and it is also beneficial to the mobile payment facilities provider into find out strategies that could improve the acceptance and use of mobile payment application.